Risk Management of Genetically Modified Organism Product: Experience from Indonesia, Malaysia, and Thailand - Oktavia, Dewi Suryani; Ardiansyah, Rhomi; Alfarisi, H.M. Salman (BIODIVERS - BIOTROP Science Magazine, 2025)
Genetically modified organisms (GMOs) have become a subject of significant debate and monitoring due to their potential implications for human health, environmental impact, and socioeconomic considerations. As a result, risk management strategies and regulatory frameworks have been developed to assess and mitigate the potential risks associated with GMOs. This review focuses on examining the current landscape of risk management approaches and regulations pertaining to GMOs. The review analyzes the key components of risk management, including risk assessment, risk communication and bioethics. It explores the role of regulatory authorities in establishing guidelines for the evaluation and approval of GMOs, ensuring their safety for human consumption and minimizing potential environmental risks. The study also investigates the involvement of international organizations in harmonizing regulations and facilitating global trade of GMO products.